The Influence of Internet Service Provider (ISP) Service Quality in Indonesia on Consumer Loyalty Through Internet User Profiles - Sri Zuliarni; Gita Rizkia Arfina (Politeknik Negeri Batam, 2025)
This study examines the effect of the quality of internet service providers (ISP) in Indonesia on consumer loyalty through the internet user profile. The population in this study are internet users and consumers (Telkomsel, Indosat, and XL) who have used the service provider for at least 1 year. The respondents used were 300 respondents located in Batam City, Indonesia. The sampling technique used was purposive method and quota sampling. This study aims to examine the dimensions of ISP service quality on consumer loyalty based on user groups (Light, Medium, and Heavy User). The data analysis technique used is SEM (Structural Equation Modeling) with SmartPLS, AMOS, SPSS, and JASP. The results of this study indicate that ISP service quality has a positive and significant effect on consumer loyalty in Indonesia. Meanwhile, the largest group of internet users is medium users.